Evaluation I: Recidivism outcomes from a management program for youth who have committed a sexual crime. Issue 6 (18th August 2017) - Brusman Lovins, Lori; Yoder, Jamie Rae; Berry, Stuart
ABSTRACT: Sexual offenders are among those most feared by society. This perception often results in removing such individuals from the community. Few studies have examined the outcomes of interventions that incorporate a comprehensive, collaborative approach between treatment and supervision providers. The current project examined the impact that efforts to manage youth adjudicated for a sexual offense ( N = 400) in the community had on public safety. Results revealed that youth supervised under a more comprehensive community-based model had a significantly lower rate of felony recidivism than youth supervised under a traditional approach. Implications for treatment and supervision are discussed.